PENERAPAN GERAKAN LITERASI SEKOLAH PADA PEMBELAJARAN BAHASA INDONESIA DI SD NEGERI COT LHEUE RHENG - Rohani Rohani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2019)
The purpose of this study was to describe the implementation of the school literacy movement program in Cot Lheue Rheng Elementary School through Indonesian language lessons by utilizing the potential of local culture. This study uses descriptive qualitative. The data collection techniques are observation and interview. The results of this study can be described that of the 5 steps in the stage of habituation of the school literacy movement in Cot Lheue Rheng Elementary School, not all steps can be taken to the full. Second, the implementation of the school literacy movement is limited to activities in the classroom. Third, the Neighborhood does not fully support this school literacy Movement program so the Environment does not provide source text as a reading. Fourth, the selection of reading books only through textbooks and assessment of community involvement has not been carried out optimally to support the school literacy movement program. Keywords: Implementation, GLS, culture, Indonesia language